Numerical investigation of constitutive material models on bonded joints in scarf repaired composite laminates. (15th March 2017) - Riccio, A.; Ricchiuto, R.; Di Caprio, F.; Sellitto, A.; Raimondo, A.
Highlights: A multi-linear elastic-plastic material model for adhesives is proposed. Equivalent stresses and strains are calculated and used as input to the FE code. The developed procedure can be used in conjunction with standard damage models. The proposed approach is effective when the shear is the predominant stress component. Abstract: The purpose of this study is the assessment of the mechanical behaviour of bonded composite repairs. An original multi-linear material model for the elastic-plastic response of adhesives is used in conjunction with an effective FE progressive damage approach for the computation of adhesive stress state within bonded joints in repaired composite structures. The proposed numerical model has been applied to several bonded joints configurations and the obtained numerical results have been compared to experimental and predicted data available in literature providing an interesting insight on bonded composite repairs. Simultaneously, a first demonstration has been given about the capability of the proposed material model to provide detailed and reliable information on the adhesive stress distribution, failure onset, and crack-path propagation.